Inquiry-based learning for the arts, humanities, and social sciences a conceptual and practical resource for educators - Blessinger, Patrick; Carfora, John M. (Bingley, U.K. : Emerald, 2014)
Inquiry-based learning (IBL) is a learner-centered and active learning environment where deep learning is cultivated by a process of inquiry owned by the learner. IBL has its roots in a constructivist educational philosophy and it is oriented around at least three components: 1) exploration and discovery (e.g., problem-based learning, open meaning-making), 2) authentic investigations using contextualized learning (e.g., field studies, case studies), and 3) research-based approach (e.g., research-based learning, project-based learning). IBL encourages more self-regulated learning because the primary responsibility is on the learners to determine the issues and research questions and the resources they need to address the questions. In this way, learning occurs across all learning domains (affective, cognitive, and social) because different types of knowledge are acquired though experience with complex, real-life problems. This volume serves as a conceptual and practical resource and guide for educators and offers practical examples of IBL in action and diverse strategies for how to implement IBL in different contexts.
Innovative approaches in teaching and learning : an introduction to inquiry-based learning for the arts, humanities, and social sciences / Patrick Blessinger, John M. Carfora -- Investigating the role of an inquiry-based approach to learning / Norman Vaughan, Steven Prediger -- A first-year social sciences inquiry course : the interplay of inquiry and metacognition to enhance student learning / Catherine Chiappetta Swanson, Arshad Ahmad, Irena Radisevic -- Inquiry-based learning for language learning : the case of French advanced level at the University of Manchester (UK) / Catherine Franc, Annie Morton -- Inquiry-based learning for interprofessional education / Elizabeth F.S. Hannah ... [et al.] -- Historical detectives at work : a casebook approach to guided-inquiry for undergraduate learning / Linda S. Watts -- Inquiry-based teaching and learning in counseling ethics education / Noor Syamilah Zakaria, Jane Warren -- Changing landscapes of education : teaching architecture through inquiry-based approaches / Aylin Yildirim Tschoepe -- Using inquiry-based learning to identify issues and develop pedagogical awareness of teaching with technology : a self-study from a pre-service teacher education class / Wendy L. Kraglund-Gauthier -- Five elements leading to better learning environments : Case Yrityslabra / Mika J. Kortelainen, Janika Kyttä, Tarja Laakkonen -- A study of inquiry-based learning in action : an example from a first-year marketing principles course / Tania von der Heidt -- Can practical wisdom be taught in business schools? An inquiry-based learning approach for management education / Claudius Bachmann -- Growing teachers for a new age : nurturing constructivist, inquiry-based teaching / Megan M. Keiser, Betsy D. Burrows, Brian Randall -- Aesthetic education and discover New York : inquiry, the arts and civic engagement / Heidi Upton -- Extending inquiry-based education in creative disciplines through assessment / J. Joseph Hoey IV, David Mills Chase, Jill L. Ferguson -- Using inquiry-based learning to teach additional languages in a high school context / Lorna Caputo -- Making historians digitally : social bookmarking and inquiry-based learning in history in higher education in the UK / Jamie Wood ... [et al.] -- Making the case for inquiry-based teaching in an economics curriculum / Barb Bloemhof -- The feasibility of inquiry-based learning : an Irish perspective. Exploring the role and motivation of inquiry-based learning in social studies : an Irish higher education experience / Aoife Prendergast -- Developing an improving stance toward research in preservice teachers / David Slavit ... [et al.].
Includes indexes.
Print version record
Keywords: Education -- General; Education; Open learning, home learning, distance education; Inquiry-based learning; Thought and thinking -- Study and teaching (Higher); Critical thinking -- Study and teaching (Higher)